Biogeografia das espécies invasoras da herpetofauna: influência de dispersores artificiais e fatores ambientais - Parreira, Caroline Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The colonization of invasive species can impact biodiversity, human well-being, health and the economy. For a species to become invasive, it must overcome biogeographical, physiological and biotic filters, therefore, the understanding of distribution patterns of introduced species is essential to support studies and preventive measures regarding the advance of bioinvasions. The present study aimed to estimate the areas of climatic suitability in Brazil, of the introduced herpetofauna species with high expansion potential, the anuran Eleutherodactylus johnstonei (Amphibia, Eleutherodactylidae) and the lizard Anolis porcatus (Reptilia, Dactyloidae), to evaluate the possible niche overlap with phylogenetically related species that are native to Brazil, and to verify which Brazilian ports are more susceptible to the introduction of Anolis porcatus, a species introduced due maritime trade. The species disitribution models (SDMs) showed that the bioclimatic variables related to temperature had the highest contributions in the model of Anolis porcatus and precipitation had the highest contributions in the model of Eleutherodactylus johnstonei, demonstrating the relationship between the distribution and the habits and characteristics of each of their respective groups. The areas where the exotic populations of these two species occur in Brazil are located in areas of minimum and low climatic suitability, according to the results of SDM. However, Anolis porcatus is rapidly expanding its distribution under these conditions, and its colonization may be more effective and accelerated when that species finds areas of higher climatic suitability. The area of endemicity results identified endemism areas of native species that overlap the areas of climatic suitability of Anolis porcatus and Eleutherodactylus johnstonei obtained with the SDM, suggesting possible future niche overlaps. The present study also found that ports of Salvador, Rio de Janeiro, Santos and Itapoá are more susceptible to new introductions of Anolis porcatus due maritime trades. Both introduced species can expand their distribution to areas where there are phylogenetically close native species and species with similar habits, and there may occur impacts on native species, which demonstrates the importance of studies about the biological interactions of these species, in addition to efforts to obtain a higher knowledge of its areas of occurrence. For Anolis porcatus, the importance of studies in port areas and its surroundings is highlighted, besides the implementation of measures within the scope of port management to prevent new introductions.

A colonização de espécies invasoras pode impactar a biodiversidade, o bem-estar humano, a saúde e a economia. Para uma espécie se tornar invasora, ela deve superar filtros biogeográficos, fisiológicos e bióticos, logo, o conhecimento dos padrões de distribuição de espécies introduzidas é essencial para subsidiar estudos e medidas preventivas relacionadas ao avanço das invasões. O presente estudo teve como objetivo estimar as áreas de adequabilidade climática no Brasil, das espécies da herpetofauna introduzidas com alto potencial de expansão, o anuro Eleutherodactylus johnstonei (Amphibia, Eleutherodactylidae) e o lagarto Anolis porcatus (Reptilia, Dactyloidae), avaliar a possível sobreposição de nicho com espécies filogeneticamente relacionadas nativas do Brasil e verificar quais portos do Brasil são mais suscetíveis a introdução de Anolis porcatus, espécie introduzida via comércio marítimo. Os modelos de distribuição de espécies (SDMs) demonstraram que as variáveis bioclimáticas relacionadas à temperatura tiveram as maiores contribuições no modelo de Anolis porcatus e a precipitação no modelo de Eleutherodactylus johnstonei, demonstrando a relação da distribuição com os hábitos e características de cada um dos respectivos grupos a que pertencem. As áreas onde as populações exóticas das duas espécies ocorrem no Brasil estão localizadas em áreas de mínima e baixa adequabilidade climática, segundo os resultados do SDM. Porém, o Anolis porcatus está expandindo sua distribuição rapidamente nestas condições, e sua colonização poderá ser mais eficaz e acelerada quando a espécie encontrar áreas de maior adequabilidade climática. Os resultados da área de endemicidade identificaram áreas de endemismo de espécies nativas que se sobrepõem às áreas de aptidão climática de Anolis porcatus e Eleutherodactylus johnstonei obtidas com o SDM, sugerindo possíveis futuras sobreposições de nicho. Constatamos também que os portos de Salvador, Rio de Janeiro, Santos e Itapoá são mais suscetíveis a novas introduções do Anolis porcatus pelo comércio marítimo global. Ambas as espécies introduzidas podem expandir sua distribuição para áreas onde existam espécies nativas filogeneticamente próximas e espécies com hábitos similares, podendo haver impactos para as espécies nativas, o que demonstra a importância da realização de estudos de interações biológicas, além de esforços para obter maior conhecimento das áreas de ocorrência. Para Anolis porcatus, destaca-se a importância de estudos nos portos e entorno, e implantação de medidas no âmbito da gestão ambiental portuária para evitar novas introduções.
Biogeography of herpetofauna invasive species: influence of artificial dispersers and environmental factors
Keywords: Biogeografia; Bioinvasão; Herpetologia; Modelo de distribuição de espécies; Áreas de endemismo; Gestão ambiental portuária; Espécies introduzidas; Biogeography; Herpetology; Species distribution models; Endemism areas; Port environmental management.; Introduced species; Bioinvasion